Peningkatan Kemampuan Memecahkan Masalah Pada Siswa Melalui Penggunaan Model Pembelajaran Group Investigation - Anis Nurfitri; Ria Herdhiana; Fugiyar Suherman (Program Studi Pendidikan Ekonomi, FKIP Universitas Langlangbuana, 2019)
This research is entitled Increasing the Ability to Solve Problems in Students Through the Use of Group Investigation Learning Models. This title was taken based on the lack of students' ability to solve business planning lessons. The main objective of this study was to obtain an overview of the improvement of problem solving skills with the Group Investigation learning model compared to varied lecture learning. Based on the results of the study, the teacher's activities during learning with the extremely expensive Group Investigation model. Data analysis was carried out quantitatively Quantitative analysis was carried out on the results of the pretest and posttest to see the difference in the mean of generalized gain between the two groups of samples and tested the nominity, homogeneity, and t test to see the difference solves the problem of the two sample groups. As well as increasing the ability to solve in the experimental class students who use the Group Investigation learning model better than the control class that uses the lecture learning model varies or design.